ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KESEJAHTERAAN PETANI DI KOTA DENPASAR - Hartati, Gusti Ayu Radi; Sri Budhi, Made Kembar; Yuliarmi, Ni Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.04.TAHUN 2017, 2017)
This study aims to analyze; 1) the impact of extensive arable land, working capital, technology and farming experience to the amount of production of sweet corn, 2) the impact of extensive arable land, working capital, technology,  farming experience and the amount of production on farmers' welfare sweet corn, 3) factor of the amount of production mediates the influence extensive arable land, working capital, technology, and the experience of farming on the welfare of sweet corn growers in Denpasar. The data sources used, there are two primary data obtained from interviews to sweet corn growers and secondary data obtained from the Department of Agriculture in Denpasar. The data collection methods used were in-depth interviews and questionnaires, with a number of respondents as many as 72 people. The analysis tool used is descriptive statistics and path analysis. The results of the analysis of that acreage and working capital positive and significant effect on the amount of production of sweet corn in Denpasar, while the technology and farming experience no significant effect Technology, acreage, working capital, and the amount of production and significant positive effect on the welfare of farmers,while farming experience no significant effect. Total production mediating influence between acreage and working capital for the welfare of farmers. The influence of technology and experience of farming on the welfare of sweet corn growers in Denpasar is not mediated by the amount of production of sweet corn.
Keywords: extensive arable land, working capital, technology, farming experience, the amount of production and welfare